Cash Flow Analysis of Mosques in Surakarta Residence, Indonesia - Fauzul Hanif Noor Athief; Anissa Hakim Purwantini; Hafizah Abdul Rahim (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2022)
Mosques have the potential to become the center of Muslim activities. This potential can be realized if the administrator can make attractive activities with the right allocation of funds. However, the absence of income and expenditure mapping based on cash flow statements affects the budgeting of planning activities. The research aims to map the cash flow to discover the budgeting possibility of the mosque. The research will be done by initially revealing the source of income and expenditure of the mosque as well as its general cash flow. By using the sample of mosque reports from each sub-district in Surakarta, this study would review the monthly financial statements of the mosques from 2016 to 2019 using content analysis. The research concluded that making budgeting out of the cash flow mapping is possible but vague since there is no clear pattern of both revenue and expenditure. Each type of mosque had a different composition of income, with Friday Shadaqah as the most significant domination for 57%. On the expense side, the Regular Expenses, Other Expenses, and Development Expenses, each contributed 1/3 of the total outcome for all types of a mosque.